Celecoxib attenuates neuroinflammation, reactive astrogliosis and promotes neuroprotection in young rats with experimental hydrocephalus - Dutra, Maurício; Covas da Silva, Stephanya; da Silva Beggiora Marques, Pâmella; Oliveira Amaral, Izadora; Funo de Souza, Stephanie Naomi; Dutra, Luiz Antônio [UNESP]; Volpon Santos, Marcelo; Machado, Hélio Rubens; da Silva Lopes, Luiza (Elsevier, 2023)
Hydrocephalus is a neurological condition with altered cerebrospinal fluid flow (CSF). The treatment is surgical and the most commonly used procedure is ventricle-peritoneal shunt. However, not all patients can undergo immediate surgery or achieve complete lesion reversal. Neuroprotective measures are valuable in such cases. It was evaluated whether the use of celecoxib, a selective inhibitor of COX-2, associated or not with ventricular-subcutaneous derivation, could offer benefits to the brain structures affected by experimental hydrocephalus. Seven-day-old male Wistar Hannover rats induced by intracisternal injection of kaolin 15% were used, divided into five groups with ten animals each: intact control (C), untreated hydrocephalus (H), hydrocephalus treated with celecoxib 20 mg/kg intraperitoneal (HTC), hydrocephalus treated with shunt (HTS) and hydrocephalus treated with shunt and celecoxib 20 mg/kg intraperitoneal (HTCS). Celecoxib was administered for 21 consecutive days, starting the day after hydrocephalus induction and continuing until the end of the experimental period. The surgery was performed seven days after inducing hydrocephalus. Multiple assessment methods were used, such as behavioral tests (water maze and open field), histological analysis (hematoxylin and eosin), immunohistochemistry (caspase-3, COX-2, and GFAP), and ELISA analysis of GFAP. The results of the behavioral and memory tests indicated that celecoxib improves the neurobehavioral response. The improvement can be attributed to the reduced neuroinflammation (p < 0.05), and astrogliosis (p < 0.05) in different brain regions. In conclusion, the results suggest that celecoxib holds great potential as an adjuvant neuroprotective drug for the treatment of experimental hydrocephalus.
Keywords: Celecoxib; Experimental Hydrocephalus; Neuroinflammation; Neuroprotection; Neurosurgery